A low gate charge field-plate trench MOSFET with hollow split gate structure. (December 2022) - Qiao, Ming; Ma, Tao; Dong, Shida; Wang, Zhengkang; Zhang, Shuhao; Li, Zhaoji; Zhang, Bo
Abstract: We propose a high-performance field-plate trench MOSFET featuring hollow split gate structure in this paper. By reducing the overlap of control gate to split gate without additional masks and preserving the stepped split gate structure, it is confirmed that the parasitic gate capacitance and gate charge are significantly reduced without changing the control gate structure and influencing the electric field distribution of drift region. Compared with the conventional two-step-oxide field-plate trench MOSFET, TCAD numerical simulation results show that gate-source charge ( Q gs ) and gate charge ( Q g ) ( V gs = 10 V) of the proposed device with a breakdown voltage of 94.32 V are reduced by 20.94% and 13.59%, respectively. Besides, breakdown voltage ( V B ) and specific on-resistance ( R on, sp ) of the proposed device remain almost constant because of the retained sidewall of hollow split gate. In addition, it is observed that the average total power loss of the proposed device is reduced by 4.60%–8.06% when frequency ranges from 100 kHz to 1 MHz in comparison to that of the conventional one.